Inequality of Opportunity in South Caucasus - Fuchs, Alan; Tiwari, Sailesh; Shidiq, Akhmad Rizal (World Bank, Washington, DC, 2018)
This paper discusses equality of opportunity in Armenia, Azerbaijan, and Georgia, with an emphasis on access to labor market opportunities. It develops an inequality of opportunity index on access to good jobs and decomposes the contributing factors in the prevailing inequality. Then, it discusses the extent to which inequality in accessing human capital inputs among individuals during the early formative years may affect access to good jobs. The main takeaways are as follows. First, connections play an important role in obtaining access to good jobs in the South Caucasus, highlighting the unfairness in processes in the sub-region's labor markets. Second, access to good jobs—defined as work for 20 hours or more a week and work under contract or with tenure—is low in the South Caucasus in comparison with other parts of Eastern Europe and Central Asia. Third, even among people who have access to these jobs, the share of the total inequality of opportunity that may be characterized as unfair is relatively high. Armenia and Azerbaijan stand out for the significant share of inequality in access to good jobs associated with gender differences. Fourth, the analysis on access to education and basic human capital inputs in the earlier, formative stages of life shows that learning performance in the South Caucasus tends to be poor and unequal across the life circumstances of children. Nonetheless, the coverage rates of basic human capital inputs are generally high; the relatively narrow inequalities arise mostly from spatial disparities. These results indicate that addressing the deep structural inequalities shaping the landscape of opportunity in the South Caucasus must be a key consideration in any strategy to share prosperity sustainably.